The development of portable GSM based direction finder prototype - Muhamad Jamil bin Jakpar (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Flood disaster which engulf Malaysia peninsular in 2014 give a big impact to the government agencies especially those who involve in search and rescue operation. Late response receives from the rescue teams cause the victims in terrible situation. For this instance, quick evacuation on the victims is vital. One big problem which faced by the rescue team is to locate the victims. Due to the current technology, the location of the victims can be uncovered through the mobile phone detection. This research aims to develop GSM1800 signal direction finder prototype. The study begins with developing a receiver which is able to detect signal in GSM1800 signal range. The receiver is used to detect the presence of GSM1800 signal. The value of the output voltage from the receiver varies with the detected signal strength and it is used as the received signal strength indicator. Through the value of receive signal strength, the distance of the signal transmitter can be estimated. This estimation can be made through the equation of free space path loss. A mathematical equation can be developed through several experiments in order to recognize the relationship between the received signal strength and the distance between the receiver and transmitter. By having a series of distance values, the triangulation technique can be applied in favour to uncover the direction of the signal source. Series of distance values are collected from the receiver which are placed in 4 appointed positions. The receiver is placed at the four positions one by one. Then, the microprocessor receives all the values of the signal strength from the receiver, convert the values into distances and compute an algorithm to estimate the direction of the signal source. After that, the microprocessor displays the result in a TFT Display Module. However, the testing was done in an indoor environment that has multiple path effects. The results had shown that the detector has successfully detect the GSM signal at a distance of up to 8m and the angles that shows the direction varies from 10 to 30 degrees. Nevertheless, the results are still acceptable as the displayed direction did not deviate much from the actual direction and still within acceptable range.